2011
DOI: 10.1007/s00595-010-4315-z
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegia due to spinal epidural hematoma after mitral valve surgery: Report of a case

Abstract: Spinal epidural hematomas are rare entities that can be associated with spinal traumatic injuries and vascular lesions or that can spontaneously arise. Several reports have linked these hematomas to heart valve surgery. We herein describe a 71-year-old female patient who developed postoperative paraplegia immediately after mitral valve repair. Magnetic resonance imaging revealed an epidural hematoma of the spinal cord from C7 to Th4. A laminectomy was not performed because the patient's paraplegia gradually im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…[92] Cases of spontaneous epidural hematoma without an epidural catheter after cardiac surgery are also described. [93][94][95][96] Hayashi et al, reported a 71-year-old women, who underwent mitral valvoplasty with CPB. [95] Surgery lasted around 4 h uneventfully, and she was not previously treated with any anticoagulant therapy.…”
Section: First Author Year Journal Surgery Epiduralmentioning
confidence: 99%
See 1 more Smart Citation
“…[92] Cases of spontaneous epidural hematoma without an epidural catheter after cardiac surgery are also described. [93][94][95][96] Hayashi et al, reported a 71-year-old women, who underwent mitral valvoplasty with CPB. [95] Surgery lasted around 4 h uneventfully, and she was not previously treated with any anticoagulant therapy.…”
Section: First Author Year Journal Surgery Epiduralmentioning
confidence: 99%
“…[93][94][95][96] Hayashi et al, reported a 71-year-old women, who underwent mitral valvoplasty with CPB. [95] Surgery lasted around 4 h uneventfully, and she was not previously treated with any anticoagulant therapy. One hour after surgery, paraplegia was noted, an epidural hematoma compressing the spinal cord at the C7-T4 level was revealed on MR imaging.…”
Section: First Author Year Journal Surgery Epiduralmentioning
confidence: 99%
“…SSEH is a rare surgical emergency and accounts for <1% of all spinal epidural lesions, with an estimated annual incidence of only 0.1/1,00,000 [11]. Precipitating factors associated with SSEH include traumatic spinal injuries, blood dyscrasia, anticoagulation therapy, spinal and epidural anesthesia, lumbar puncture, Paget's disease, tumor genesis, and arteriovenous malformation [12, 13,14]. Therefore, etiology of SSEH in our case may be anticoagulant therapy due to mitral valve replacement.…”
Section: Discussionmentioning
confidence: 99%